Sky High or Grounded: Nest Site Selection of Herons and Egrets in a Mixed‐Species Colony - Farrah Samraoui; Riad Nedjah; Abdennour Boucheker; Hamed A. El‐Serehy; Boudjéma Samraoui (Ecology and Evolution)
ABSTRACT Resource partitioning is crucial for the coexistence of colonial herons, as it allows multiple species to share the same habitat while minimising competition. This study took advantage of a natural experiment in 2006 and 2007 when Black‐crowned Night Herons were prevented from breeding at Lake Fetzara in the first year due to the presence of a feral cat. This event provided valuable insight into the spatial and temporal dynamics of nest site selection among coexisting heron species, which consisted of Cattle Egrets (Ardea ibis), Little Egrets (Egretta garzetta) and Squacco Herons (Ardeola ralloides). After the cat was removed, egg‐laying began in the core areas of the colony and gradually spread to the periphery. Species that initiated nesting early selected mid‐elevation sites near the tree trunk, which likely offered protection from both ground and aerial predators, while also providing some shielding from solar radiation and strong winds. These early selected sites featured larger branches, which conferred greater nest stability. Vertical stratification was evident among the heron species; however, contrary to long‐standing assumptions, it was not directly related to body size. Both vertical and horizontal stratification were observed, with nests progressively moving higher and further from the tree trunk as the breeding season advanced. The following year, Black‐crowned Night Herons displaced other species to lower heights and positions further from the trunk, highlighting the significant influence of interspecific interactions on nest site selection. This study underscores the complex interplay between nest site selection, biotic interactions and abiotic factors in heron colonies, emphasising the importance of resource partitioning in maintaining species coexistence in densely populated breeding sites.